Recommendations on Raising Operative Efficiency of Budget Funds Use - M. E. Kosov; O. V. Makashina; O. V. Staroverova (Вестник Российского экономического университета имени Г. В. Плеханова)
In the current situation the interest of legislative and executive powers in efficiency of budget funds use becomes more evident. The authors of the article put forward recommendations in such aspects as upgrading organizationmethodological and statutory-legal support, extending informational base and improving accuracy of cash forecast. The most important finding of the research is the author’s model of cash forecast based on real daily data of the Federal Treasury. The experience of developing a specialized information resource for cash forecast gives an opportunity not only to respond quickly to requests of irregular expenses connected with elimination of emergency situation effects, court rulings, etc, but also to accumulate daily information for a number of years, which forms the condition for more accurate forecasts. In the research methods of systemic analysis and forecast were used. To prepare recommendations on raising operative efficiency data on revenues and expenses of budgets in the budget system of Russia in 2020–2024 were used. The principle tools for analyzing data were specialized applications and technical means.